Herrnhut : the formation of a Moravian community, 1722-1732 - Peucker, Paul, 1963- (Pietist, Moravian, and Anabaptist studies., 2022)
"Examines the early years of Herrnhut religious community and places its development in the context of German Pietism of the early eighteenth century"--